Origins of objectivity - Burge, Tyler (Oxford : Oxford University Press, 2010)
Tyler Burge's study investigates the most primitive ways in which individuals represent the physical world. By reflecting on the science of perception and related psychological and biological sciences, Burge outlines the constitutive conditions for perceiving the physical world, thus locating the origins of representational mind.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Objectivity